Toward translingual realities in composition: (re)working local language representations and practices - Bou Ayash, Nancy, author; Utah State University Press, publisher (Colorado State University. Libraries, 2019)
A multi-year ethnographic study of first-year writing programs in Lebanon and Washington State--respectively, a country where English isn't the language of instruction and a state in which English is dominant--to examine the multiple and contradictory manifestations of language ideologies.--Provided by publisher.
Language ideologies in teaching writing -- Working translingual language representations and/as practices -- Local language representations and/as practices unpacked -- Unpacking local language representations and/as practices continued -- Translingual activism.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); English language -- Social aspects -- Lebanon -- Beirut; English language -- Social aspects -- Washington (State) -- Seattle; Language and culture; Academic writing